People's team, struggling and freedom: the symbolic constructions of Sport Club Corinthians Paulista strengthened by Democracia Corinthiana - Marques, Jose Carlos [UNESP]; Azevedo, Nubia Maria Silva de [UNESP]; Tsutsui, Ana Lucia Nishida [UNESP] (Univ Federal Sergipe, 2023)
Carrying lots of symbolic factors, soccer in Brazil transcends the limits of sports itself and becomes an important social tool. From a cultural and political perspective of soccer, this article aims to analyze the affective manifestations around Corinthians Paulista, questioning how the symbolic constructions potentiated by Democracia Corinthiana (Corinthians Democracy) reverberate in the team's beliefs and behaviours. Methodologically, the study is based on bibliographical research, discursive textual analysis, and content analysis. The article concludes that the team, in order to legitimize itself, makes use of episodes from its history, building for itself an identity based on the concepts of people, struggle and freedom.
Keywords: Soccer; Policy; Symbolic Constructions; Corinthians Democracy